Spectroscopic studies of humic acids from subsurface sediment samples collected across the Aegean Sea - SAKELLARIADOU, F. (Mediterranean Marine Science, 2006)
Natural humic acids are biogenic, structurally complex and heterogeneous, refractory, acidic, yellow-to black-coloured organic polyelectrolytes of relatively high molecular weight. They occur in all soils, sediments, fresh waters, and seawaters. Humic acids represent the largest portion of nonliving soil organic matter. In the present paper, humic substances were isolated from marine subsurface sediment samples collected across the Aegean sea (in Greece) and especially from a marine area extending northwards of the Samothraki plateau towards the north-eastern part of the island of Crete. In a following step, humic preparations were studied using infrared and fluorescence spectroscopy (emission, excitation and synchronous-scan excitation spectra were obtained). The infrared spectra suggested functional chemical groups such as as OH-, C-H aliphatic, C=C, C=O/COO-, salts of carboxylic acids, and also, in some cases, silicate anions or C-O from alcohols, esters and ethers. Fluorescence emission, excitation and synchronous scan excitation provided some valuable information concerning a probable origin (marine and/or terrestrial) for the isolated humics.